La reforma electoral: análisis y perspectivas (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2011)
The electoral reform recently carried out is probably one of the most important modifications introduced in the 25 years of effect of the Organic Law for the General Election Regime (LOREG). It certainly has implied a deeper study to analyse potential changes that could improve the electoral system.This paper examines the said reform. It analyses the complex process leading to the introduced modifications: three law proposals and many international treaties signed and ratified by Spain. This paper also studies the real changes. For some, it is all that could be done at the moment; for others, the reform introduces only minor changes that hardly tackle the problems raised by our electoral system.The main points of the reform examined in this paper are the following: the method used for recognizing voting rights to foreign residents in municipal elections; the reform of Senate ballot papers; the amendments concerning electoral roll to prevent fraudulent or convenient registrations; the new voting system for Spanish nationals living abroad; changes introduced in election campaigns to avoid interference of the public power and try to reduce propaganda and electoral publicity; reforms in the municipal electoral system, particularly, to prevent changes of allegiance and regulate the voting model. And lastly, we analyse the reform to complement the Political Parties Law regarding the prosecution of parties acting in concert with a terrorist group.